Design Criteria of Learning Space for Street Children: The Observe Rituals Method - Faniah Shafira Amir Ishak; Fransiscus Xaverius Teddy Badai Samodra (Institut Teknologi Sepuluh Nopember, 2020)
An essential dimension for street children in coaching and learning in urban areas like Surabaya is the independence of learning in individual street children who are related to their privacy needs. Awareness of these privacy needs can be done with a perception approach that will vary from one person to another. The appropriate form of architecture as an attempt to deal with the problem of street children in Surabaya is a learning space. The main target and scope of the learning space are in the city of Surabaya, with a dense urban range and high economy. The method used in the search for design criteria is the observe rituals method. The process starts by observing and recording in detail the various events in a setting. Search for design criteria in this study as data to be implemented in a force-based framework, which is then reviewed to produce a learning space architecture design. The movement and performance of children in the learning process is a significant factor in the search for learning space design criteria. The results showed that moveable, active, open, theatrical, and excited were essential factors to produce design criteria.